Analisis Kualitatif Konsistensi Pencatatan Rekam Medis Rawat Inap Kasus Penyakit Dalam di Rumah Sakit Pelabuhan Jakarta - Putri Nurindahsari; Dina Sonia; Lily Widjaja; Daniel Happy Putra (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2023)
Qualitative analysis is an activity that examines the filling of medical records for inconsistent and incomplete contents, which indicates that the medical records are inaccurate and incomplete. The purpose of this study was to find out a qualitative analysis of the reliability of recording medical records of inpatient cases of internal medicine for the year 2022. This type of research uses a descriptive method with a quantitative approach and data collection by observation and interviews. Of the 99 medical records, the results obtained were 96% consistent and 4% inconsistent. And the results of the 4 subcomponents include: At the time of admission, namely the consistency of the initial assessment of nurses and inpatient doctors, the results were 98% consistent. On the subcomponent during hospitalization, namely the consistency of progress notes between doctors and nurses, obtaining results of 99% consistency, Consistency of Doctor's Instructions with delivery notes the drug gets 93% consistent results, when going home, namely the consistency of the doctor's return summary and the nurse gets 94% consistency results. Of the 4 sub-components that have the highest consistency, the consistency between the doctor's and nurse's developmental records obtains 99% consistent results. While the lowest was the consistency of the Doctor's Instructions with a record of drug administration obtaining 93% consistent results. The conclusion is that the qualitative analysis of medical record recording is not 100% consistent. It is recommended that the Jakarta Harbor Hospital make standard operating procedures and implement related qualitative analysis of medical records.